ANALISIS PROFIL MULTIPEL REPRESENTASI MAHASISWA PADA MATA KULIAH ANALISIS RIIL BERDASARKAN PRINSIP-PRINSIP TEORI BELAJAR DAVID AUSUBEL - Nizaruddin .; Nurina Happy; Yanuar Hery M (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2015)
The research with the tittle is ?óÔé¼?ôProfile Analysis of Students Multiple Representation on Real Analysis Subjects based on The Principle of Learning Theory by David Ausubel?óÔé¼?Ø has purpose to describe profile of students multiple representation based on the principle of learning theory by David Ausubel. This reserach is qualitative-exploratif research. Qualitative research because the procedure produce descriptive data that is written or spoken words from subject of research, and explorative research because this research express students profile of multiple representation on solving problem in real analysis subject. The data of this research got from written students?óÔé¼Ôäó work on solving problem of real analysis problem based on the principle of meaningfull learning and interview transcript from research subject. There are three subject in this research that have different level of self-efficacy. The location of research is in mathematics education study program, PGRI Semarang University. The result of this research are the multiple representation of subject with medium (M3) and low (M4) level of independecy is not shown, but the multiple representation of subject with high independency (M2) can be shown in verbal and picture representation. The dimention of thinking based on meaningfull learning by David Ausubel that are: the dimention of thinking with procedure orientation, process orientation, object orientation, concept orientation and versalite can not shown on subject with low and medium level of indenency, but the diemention of thinking with process. concept, object orientation can be shown on subject with high level of independency. The versalite stage is not shown by subject with high, medium, and low level independency, but they can shown the stage of conceptual thinking. So, the multiple representation based on the principle of meaningfull learning by David Ausubel with different indenency level can be shown on subject with high level independency. ?é?á Keywords: Multiple Representation, Real Analysis, Learning Theory of David Ausubel